Les relations entre les cités béotiennes à l’époque archaïque - Katerina Meidani (Kentron, 2008)
By searching the reasons why Plataians had recourse to Kleomenes’ aid in 519, the author studies the relationships between Boeotian cities, and particularly the conflicts between Thebans and Plataians. Now, while examining the reasons why Boeotian cities were led to establish an alliance, which foreshadowed the Boeotian Confederacy, the author establishes the following point: before 508/507, when Thebans invaded Attica with Spartans for the first time as “Boeotians”, they had not formed a Boeotian Confederacy under their domination yet, contrary to what is often said.